Character Card : Media Penguatan Pendidikan Karakter di SMP Negeri 6 Meureubo - Shinta Riski Amanda; Yusril Sahendra; Muhammad Aydil; Muhammad Farizal Ahyar; Johan Khadafi; Opelia Ika Sahara MT; Widia Nira Wati; Rika Musrianti; Sari Dewi; Nurhilma Nurhilma; Dian Prisda; Fatimah Hijrah; Maysarah Nadia Ulfa; Rizki Fitria (Universitas Teuku Umar, 2023)
Character education is an obligation that schools must carry out for students as an effort to shape the character of students in the era of digital technology development. This activity was carried out at SMP Negeri 1 Meureubo with the aim of (1) increasing students' understanding of the values in character education; (2) Designing or designing Character Card media as a learning model for implementing character education programs; and (3) Forming digital literacy cadres in implementing character education programs. The method used is (1) The planning and preparation stage, namely the design of Character cards as one of the media used by the service team in outreach; (2) The implementation stage is to provide socialization material about character education values to students; and (3) Evaluation Stage. The target group in this activity was 30 combined students from grades 7 and 8. The results of this activity obtained a significant change from before the intervention was carried out. After the intervention, there was a change in the number of students who had knowledge and skills of character values consisting of the aspect of caring for the social environment there are (27 students), elements of peace-loving behavior (28 students), characteristics of religious attitude (25 students); and aspects of creativity (29 students). This service activity also forms the school's commitment to continue this program to improve school character educatio